Library Service Innovation in Increasing Accessibility of Information for Users from the Perspective of Librarians and Users at the Batam Institute of Technology Library - Dewi, Anisa Prima (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
Libraries play a crucial role in disseminating information to society. However, the challenges of the digital era have increased the need for innovative services to remain relevant. The transformation from manual to digital services is a strategic step, including providing access to digital information resources, utilizing social media, and online learning platforms. Digital technology facilitates access to up-to-date information, enhances literacy, and broadens service reach. Innovations such as digitizing collections, online borrowing services, information literacy programs, and mobile application development can significantly boost user engagement. For instance, Universitas Teknologi Batam Library offers various innovative services to meet users’ information needs. Libraries’ adaptation to technological advancements and evolving user demands is essential to maintaining high-quality services. These innovations ensure libraries remain relevant, expand access to information, and support improved literacy among the public. Adaptation and innovation are vital steps for libraries in the digital era.